Perception of the people of the community of Cabeça de Boi - Itambé do Mato Dentro (MG) and tourists that visit the region on impacts understood by tourism activity (Research, Society and Development, 2019)
Ecotourism represents a segment of tourism that uses sustainable natural resources, seeking to encourage conservation of these and promote the well-being walfare of the population. In this sense, the Cabeça de Boi community, located in the city of Itambé do Mato Dentro (MG), corresponds to a place commonly sought wanted by tourists given the existence of several natural tourist attractions, such as the waterfalls of Intancado, Maçã, Chuvisco, in addition to Lajeado and Poço. Thus, this research aimed to identify the perception of the residents perception of this community and the tourists who have visited the region in the period of this research about the impacts triggered by the tourist activity. For this, using a qualitative and quantitative approach, 15 residents were interviewed, and questionnaires were applied to 182 tourists. Considering the perception of the residents perception of the community regarding tourism, it is highlighted as a positive impact the generation of employment, however, a significant part of the interviewees did not has not recognized that this activity had negative environmental impacts. It should be noted that most of the tourists who attended the region corresponded to the young and adults, having a higher education level. In relation to the tourist elements considered positive by the tourists can be highlighted the gastronomy and the quality of the service quality; In turn it was necessary to adequate the signage and the cleaning of the attractions. Thus, it is noted that the planning of tourism is essential for the community, since it aims to reduce negative impacts, promote the conservation of tourist attractions and foster local economic development.